Sustainable nation urban design patterns for the world we want - Farr, Douglas (John Wiley & Sons, Inc., 2018)
The bestselling guide to forward-looking urban planning and design Sustainable Urbanism explores and celebrates innovation in sustainable living, and calls for leadership in the design and development of urban spaces. Sustainable Nation seeks to shift the sustainability conversation towards the issue of how to change faster than ever before. It is an ideal guidebook for urban designers, planners, policymakers, architects, engaged stakeholders, and anyone who is eager to make a positive impact on our-and our descendants'-buildings, cities, and lives.